Comparative clinical characteristics of untreated early rheumatoid arthritis in patients with early and late onset according to the All-Russian Register of Patients with Arthritis “OREL” - A. M. Satybaldyev; N. V. Demidova; G. I. Gridneva; N. Yu. Nikishina; E. V. Gerasimova; K. A. Kasumova; A. S. Misiyuk; O. A. Rumyantseva; E. A. Strebkova; V. N. Sorotskaya; N. V. Chichasova; E. L. Nasonov (Научно-практическая ревматология)
The question about the peculiarities of the course of rheumatoid arthritis in different age periods was raised in the literature repeatedly and the answer depended on the period of development of rheumatology and was not unambiguous. The course of age-specific features of the initial stages of disease development has also been studied (although less frequently). At the same time, the issues of age-related features of as yet untreated early rheumatoid arthritis have not been previously presented in the literature studied by the authors. This article gives a brief overview of the problem and discusses the findings.The aim of the present study was the comparative study of the characteristics of untreated early rheumatoid arthritis with early (18–49 years) and late (50 years and older) onset.The material was represented by 292 patients with rheumatoid arthritis with disease duration from 1 to 12 months from the disease onset, entered into the All-Russian Register of Patients with Inflammatory Arthritis “OREL” in the period from January 01, 2012 to December 31, 2018 with the results of examination at the time of the first examination. All patients were naïve to treatment with basal (synthetic, biological or other targeted) drugs and systemic glucocorticoid therapy. In 141 patients, the disease started at a younger age, group 1 (18–49 years), and in 151, at an older age (50 years or older), group 2.Methods. Disease activity (according to DAS-28 index), radiological stage – (according to Steinbroker, modified), functional disorders – according to functional class, immunological characteristic and additional immunological characteristic (rheumatoid factor, cyclic citrullinated peptide antibodies) and other parameters were estimated in accordance to requirements of current national rheumatoid arthritis classification. The results of the study indicate that the disease in older age is characterized by more pronounced inflammatory, destructive changes in relation to the joint apparatus and functional disorders than the onset of rheumatoid arthritis at a young age.